More Than Skin Deep? The Effect of Visible Tattoos on the Perceived Characteristics of a Rape Victim - Wasarhaley, Nesa E. (Women & criminal justice, 2020)
The present experiment examined whether negative tattoo stereotypes would cause negative judgments about a rape victim. Mock jurors (N = 174) read an acquaintance rape trial summary online and viewed a photo depicting the alleged victim with a feminine (flower), neutral (script), or no tattoo. They rendered verdicts and rated the victim on various attributes (e.g., credibility). Overall, participant gender was the strongest predictor of trial judgments and ratings of victim attributes. Additionally, participants blamed a victim with a flower tattoo less (vs. script), which increased guilty verdicts in this condition. Results are discussed with regard to the effect of extra-legal factors on rape judgments.